Pengembangan Modul Pembelajaran Berbasis Teknologi untuk Guru Pada PKBM An-Nadhif, Cikeusal, Kabupaten Serang - Rangga Galura Gumelar; Ikhsan Ahmad; Iman Mukhroman (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Community service is a form of real contribution from academics in helping to solve problems in the community. One of the relevant activities is training in making technology-based learning modules for teachers at the An-Nadhif Community Learning Centre (PKBM), Cikeusal, Serang Regency. In today's digital era, the use of technology in education is very important. Therefore, this activity aims to improve teachers' competence in developing teaching materials that are interesting, effective, and in accordance with the needs of students. For example, through this training, teachers can utilise online learning applications to create more dynamic interactions with students. Thus, not only teaching materials are delivered, but also a more enjoyable learning experience for learners. In-depth analysis shows that a good module should consider various aspects, such as students' learning styles and their socio-cultural context. In conclusion, the development of technology-based learning modules at PKBM An-Nadhif not only improves the quality of teaching, but also contributes to improving the quality of education in the community as a whole